(untitled) (Boletin Médico de Postgrado, 2020)
In order to describe LigaSure® use for sealing of the cystic duct in patients who undergo laparoscopic cholecystectomy in the Sociedad Anticancerosa del Estado Lara during the period June 2012-June 2017 we conducted a descriptive transversal study with retrospective data collection of 62 medical charts. Results show that the average patient age was 47.58 ± 14.11 years with a female predominance (64.52%) and an average surgical time of 41.74 ± 7.99 minutes. There was no intraoperative or postoperative complications and the postsurgical stay in 77.42% of patients was 24 hours. In conclusion, the use of LigaSure® for cystic duct sealing is a safe technique for patients who undergo laparoscopic cholecystectomy.